2012
DOI: 10.1021/jz300225n
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of the Compressed Gas on Melting Point of Liquid Confined in Nanospace

Abstract: Phase behaviors of the liquids in nanospaces are of particular interest to understand the thermodynamics of the liquid on the nanoscale and for their applications that involve the confined systems. However, in many cases, the inconsistent observations of melting point variation for confined liquids are often revealed by different groups. Ionic liquids are a special kind of liquid. Here, by using the merits of the nonvolatile nature of ionic liquids, we realized the encapsulation of ionic liquids inside of meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 26 publications
1
59
0
Order By: Relevance
“…15 Our previous research proved that RTILs confined within CNTs formed polymorphous crystals at a melting point of >200°C. 16 We also demonstrated that gas compression during RTIL loading in nanospace 17 and the diameter of the basic material 18 considerably affect the structural and dynamic properties of the confined ILs. This unusual thermal transition and crystallization in the nanometric system are strongly influenced by geometric constraints and strong interactions between the solid and fluid, as explained by the Gibbs− Thomson equation.…”
Section: Introductionmentioning
confidence: 81%
“…15 Our previous research proved that RTILs confined within CNTs formed polymorphous crystals at a melting point of >200°C. 16 We also demonstrated that gas compression during RTIL loading in nanospace 17 and the diameter of the basic material 18 considerably affect the structural and dynamic properties of the confined ILs. This unusual thermal transition and crystallization in the nanometric system are strongly influenced by geometric constraints and strong interactions between the solid and fluid, as explained by the Gibbs− Thomson equation.…”
Section: Introductionmentioning
confidence: 81%
“…The decomposition temperature, which indicates the thermal stability of the ionic liquid, can also be affected by the interface interaction. For example, it was observed that the decomposition temperature of the [BMI][PF 6 ] decreased by 80 °C when the IL was confined in a nonthermal conducting porous silica with pore size less than 10 nm . The reason for this decrease is yet unclear.…”
Section: Ile‐scesmentioning
confidence: 99%
“…Nanoconfined ILs constitute therefore a new class of composites, where the confinement effects and the interactions between the ILs and the pore walls of the porous solid networks modify their physicochemical properties compared to the corresponding bulk system. For example, an increase or decrease 24 of the melting point of ILs compared to the bulk state has been experimentally demonstrated under confinement, depending on the nature of the ILs 25 , on the surface chemistry of the solid interface 26,27 , or on the environmental conditions 28 .…”
Section: Introductionmentioning
confidence: 99%